The archaeology of Mapela Hill, South-Western Zimbabwe - House, Michelle (Department of Archaeology, 2016)
The Middle Iron Age in southern Africa has long been associated with the development of class distinction and state formation. However, most research focus has been on K2 and Mapungubwe in the Middle Limpopo Valley, the presumed first state capitals of the region. Mapela Hill is a site located outside the Middle Limpopo in south western Zimbabwe. Preliminary excavations at the summit of the hill by Peter Garlake in 1968 has resulted in archaeologists drawing contrasting conclusions about the position of the site in the development of complexity in the region. The problem is that we do not have sufficient evidence to support nor deny these theories. As a result of excavations from the foot of the hill to the hill summit, this study has used a combination of theories and analyses in order to classify the material cultural objects recovered at Mapela Hill. Ceramic studies have been used to identify the cultural groups which occupied the site, and tight radiocarbon dates were established, giving insight to the chronology of the site. The results showed that Mapela Hill was occupied by the same groups as at Mapungubwe Hill, contains vast revetment stone walling, successions of thick solid dhaka hut floors and an abundance of traded glass beads; attributes which collectively signify state formation in the region. The radiocarbon dates revealed that the site was occupied before, during and after the abandonment of Mapungubwe Hill. These results call for more research at relatively unknown sites in the region as a progression towards new frameworks for the development of state formation in the Shashe Limpopo confluence